Infiltrative Hepatocellular Carcinoma With Portal Vein Tumor Thrombosis Treated With a Single High-Dose Y90 Radioembolization and Subsequent Liver Transplantation Without a Recurrence. Issue 9 (September 2017) - Dendy, Meaghan S.; Camacho, Juan C.; Ludwig, Johannes M.; Krasinskas, Alyssa M.; Knechtle, Stuart J.; Kim, Hyun S.
Abstract : Background: Infiltrative hepatocellular carcinoma with macrovascular invasion is a relatively rare presentation and usually fatal disease. Methods: Both patients exceeded Milan and University of California-San Francisco (UCSF) criteria, and per Barcelona Clinic Liver Cancer group guidelines, they were enrolled in a prospective open-label radioembolization phase II trial that gave them optimized lobar doses of Yttrium-90 as solely the first-line therapy without concomitant or additional pharmacological or locoregional therapies. Results: Three months after radioembolization, the patients demonstrated no residual viable disease on surveillance imaging. The patients were then followed up with serial imaging for 2 years in 3-month intervals, without documenting recurrence or extrahepatic disease. Finally, both patients underwent transplantation and after more than 20 months of imaging surveillance, no locoregional or systemic recurrence have been observed. Conclusions: We present, to our knowledge, the first 2 reports of transplantation after successfully downstaging infiltrative disease with portal vein tumoral thrombosis, which traditionally poses as a relative contraindication for resection or transplantation.